Some Common Non-Timber Forest Products Traded by Indigenous Community in Sabah, Malaysia - Julius Kodoh; Andy Russel Mojiol; Walter Lintangah (Canadian Center of Science and Education (CCSE), 2009)
The survey showed that a total number of 109 species of NTFPs were traded locally in the tamu (open market), comprising 35 species of wild edible plants, 32 species of medicinal plants, 8 species of orchids, 4 species of bamboos, 6 species of rattans, 8 species of fish, 8 species of wild fruit trees and 8 species of other products. This survey covered ten most common tamu and major ethnic groups in Sabah, mainly Kadazandusun, Rungus and Murut.